Analisis Faktor-Faktor Pengambilan Keputusan Terhadap Konsultan Pajak - Rusdi Hidayat; Acep Samsudin; Rista Adhalia Fani; Mia Dwi Risandi; Intan Dwi Isma Saputri; Nur Annisa Fatiha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The objective of this study is to identify the different factors that influence the decision-making process of the tax advisor. The method used in this research calls upon literature and bibliographical studies. The author uses various reviews, the discussion of which is always important and used as reference material in the creation of these reviews. The results of this study indicate that perceptions of Machiavellianism, ethics of social responsibility, situational factors, and locus of control have a positive impact on professional tax decisions. The research may be used as reference material for other researchers. Keywords: